Decitabine Enhances Vγ9Vδ2 T Cell-Mediated Cytotoxic Effects on Osteosarcoma Cells via the NKG2DL–NKG2D Axis - Wang, Zhan; Wang, Zenan; Li, Shu; Li, Binghao; Sun, Lingling; Li, Hengyuan; Lin, Peng; Wang, Shengdong; Teng, Wangsiyuan; Zhou, Xingzhi; Ye, Zhaoming (Frontiers in Immunology, 2018)
γδ T cell-based immunotherapy for osteosarcoma (OS) has shown limited success thus far. DNA-demethylating agents not only induce tumor cell death but also have an immunomodulatory function. In this study, we have assessed the potential benefit of combining decitabine (DAC, a DNA demethylation drug) and γδ T cells for OS immunotherapy. DAC increased the expression of natural killer group 2D (NKG2D) ligands (NKG2DLs), including major histocompatibility complex class I-related chains B (MICB) and UL16-binding protein 1 (ULBP1), on the OS cell surface, making the cells more sensitive to recognition and destruction by cytotoxic γδ T cells. The upregulation of MICB and ULBP1 was due to promoter DNA demethylation. Importantly, the killing of OS cells by γδ T cells was partially reversed by blocking the NKG2D receptor, suggesting that the γδ T cell-mediated cytolysis of DAC-pretreated OS cells was mainly dependent on the NKG2D–NKG2DL axis. The in vivo results were consistent with the in vitro results. In summary, DAC could upregulate MICB and ULBP1 expression in OS cells, and combination treatment involving γδ T cell immunotherapy and DAC could be used to enhance the cytotoxic killing of OS cells by γδ T cells.